Prototype Alat Pengaman Sepeda Motor Berbasis Arduino Uno Terintegrasi GPS, Notifikasi dan Kontrol Melalui SMS - Seftiani, Yudia (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
Motorbike theft is increasing, causing concern and losses for vehicle owners. Preventing motorbike theft can be done by creating a prototype of an innovative motorbike safety device based on Arduino Uno which integrates global positioning system (GPS) technology, notifications and distance control via short message service (SMS). This tool uses Arduino Uno as the main control brain, with a NEO-6M GPS module to obtain accurate location information. The SIM800L V2 GSM cellular communications module is integrated to transmit location data and receive commands via SMS. Passive infrared (PIR) sensors for movement detection are also implemented to detect and respond to theft attempts. The system can provide notifications to motorbike owners via SMS messages when suspicious events occur, such as unwanted movements or attempted theft. Users can control certain functions such as turning off the vehicle using a relay as an electrical breaker in the vehicle. Tests are carried out to ask about location, notification response speed and general security of the tool. Testing the tool was carried out in several steps, firstly testing the SIM 800L function to see the cellphone's access speed in receiving signals, secondly testing the GPS NEO-6M to see the speed of accessing map sending, thirdly testing when the motorbike was moved to a certain point. This will see how fast the tool is designed to send signals via SMS. Based on tests carried out, this tool provides a fast response in the range of 8 to 80 seconds. Test results show that this tool can provide an effective handheld and innovative solution to improve motorbike safety through the advantage of simple but efficient technological integration.